1999
DOI: 10.1086/315072
|View full text |Cite
|
Sign up to set email alerts
|

Early CD69 Expression on Peripheral Blood Lymphocytes from Children with Dengue Hemorrhagic Fever

Abstract: Recent reports have demonstrated immune activation in dengue hemorrhagic fever (DHF) by cytokine and soluble receptor detection in blood. The goal of this study was to determine which cell types are activated and likely to be responsible for cytokine production. Whole blood specimens from 51 Thai children presenting within 72 h of fever onset and with detectable plasma dengue viral RNA were studied by flow cytometry. Absolute CD4 T cell, CD8 T cell, NK cell, and gammadelta T cell counts were decreased in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
183
3
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(213 citation statements)
references
References 35 publications
25
183
3
2
Order By: Relevance
“…T cell lines also were used to study the IFN-g response of Vd2 2 gd T cells to fibroblasts infected with CMV (19). It was reported that the activation marker CD69 is upregulated on gd T cells during dengue infection (20). However, the extent to which primary human gd T cells can rapidly contribute to the anti-DV response by IFN-g production or cytotoxicity is unknown.…”
mentioning
confidence: 99%
“…T cell lines also were used to study the IFN-g response of Vd2 2 gd T cells to fibroblasts infected with CMV (19). It was reported that the activation marker CD69 is upregulated on gd T cells during dengue infection (20). However, the extent to which primary human gd T cells can rapidly contribute to the anti-DV response by IFN-g production or cytotoxicity is unknown.…”
mentioning
confidence: 99%
“…Cytokines that may induce plasma leakage such as interferon g, interleukin (IL) 2, and tumour necrosis factor (TNF) are increased in DHF cases [20,21]. Also, interferon enhances uptake of dengue particles by target cells through increasing Fc cell receptors [22].…”
mentioning
confidence: 99%
“…The timing of expression of CD69 in this cohort was consistent with previous reports. 13 While Akondy et al 39 reported that CD38, HLA-DR and Ki-67 are specific markers of activation when present in combination, there were a significant proportion of cells that expressed only CD38. Friberg et al 33 found lower intensity of CD38 expression on influenza tetramer-positive cells compared with A11-NS3 133-142 tetramer-positive cells during DENV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used a number of cell surface markers to phenotype CD8 + T cells in DENV infection. 12,13,26,33,38 We included a diverse panel of surface markers including some that have not previously been studied in DENV infection, such as CD71. The timing of expression of CD69 in this cohort was consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation